2018
DOI: 10.21608/edj.2018.78432
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Middle Mesial Canals in the Mesial Root of First Permanent Mandibular Molars in Egyptian Population: An Invivo Cohort Retrospective Cone-Beam Computed Tomographic Study

Abstract: Objective: The aim of the study was to detect the prevalence of middle mesial canals in the mesial root of first mandibular molars in Egyptian population by retrospective analysis of a large number of cone-beam computed tomography (CBCT) scans. Materials and Methods:A total of 1090 CBCT scans of first permanent mandibular molars were obtained from patients who visited the Faculty of Dentistry, Cairo University, Egypt, for various purposes. CBCT scans were searched and only 800 subjects (374 males and 426 femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The meta-analysis showed that the prevalence of MMC in females (13.961%) was significantly higher than that in males (9.798%). This result is in accordance with several studies that reported a higher prevalence of MMC in females than in males ( Bhatti et al, 2022 , Pan et al, 2019 , Roshdy and El Khodary, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The meta-analysis showed that the prevalence of MMC in females (13.961%) was significantly higher than that in males (9.798%). This result is in accordance with several studies that reported a higher prevalence of MMC in females than in males ( Bhatti et al, 2022 , Pan et al, 2019 , Roshdy and El Khodary, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, another study showed a 4.5% MMC prevalence in mandibular first molars ( Sajjan et al, 2021 ). In contrast, a higher prevalence of MMC in mandibular first molars was reported by several studies to vary from 10.8% to 59% ( Akbarzadeh et al, 2017 , Bhatti et al, 2022 , Hu et al, 2019 , Inaty et al, 2020 , Roshdy and El Khodary, 2018 , Senthil and Solete, 2021 , Srivastava et al, 2018 ). This could be explained by the differences in CBCT evaluators, CBCT devices used, and sample sizes included in their studies.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This could be explained by differences in sample size, microCT scanning parameters and the classification used for interpretation. Another CBCT study reported 25.6% of MMCs in mandibular first molars of Egyptians 35 . Indeed, the high accuracy of microCT scanning allows more detection of fine MMCs compared to CBCT.…”
Section: Discussionmentioning
confidence: 96%